Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1177/1524838016659489
|View full text |Cite
|
Sign up to set email alerts
|

Polyvictimization Among Children and Adolescents in Low- and Lower-Middle-Income Countries: A Systematic Review and Meta-Analysis

Abstract: Experiences of polyvictimization among children and adolescents in LALMIC are more prevalent than in high- and upper-middle-income countries and contribute to the burden of poor health among children and adolescents. Most LALMIC lack local data, and research is required to address this knowledge gap.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
3
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 56 publications
4
80
3
2
Order By: Relevance
“…The timing of exposure also may matter; for instance, the SRH effects of IPV before versus during pregnancy may differ (Islam, Broidy, Mazerolle, Baird, & Mazumder, 2018). To create interventions, a better understanding of polyvictimization against girls and women in LMICs will be essential (Grose et al, 2019;Le, Holton, Romero, & Fisher, 2018;Yount et al, 2017).…”
Section: Scope Of Gbv Exposuresmentioning
confidence: 99%
“…The timing of exposure also may matter; for instance, the SRH effects of IPV before versus during pregnancy may differ (Islam, Broidy, Mazerolle, Baird, & Mazumder, 2018). To create interventions, a better understanding of polyvictimization against girls and women in LMICs will be essential (Grose et al, 2019;Le, Holton, Romero, & Fisher, 2018;Yount et al, 2017).…”
Section: Scope Of Gbv Exposuresmentioning
confidence: 99%
“…Recent studies suggest that social learning also play an important role in the transmission of maladaptive fears and anxiety, such as those occurring in anxiety disorders and posttraumatic stress [9, 18, 20, 7484]. In particular, clinical research shows that many phobias may be acquired through social transmission, either observational or instructed [85].…”
Section: Social Learning and Transmission Of Maladaptive Fears And Anmentioning
confidence: 99%
“…According to a meta-analysis including 30 articles, the pooled lifetime prevalence of any of these self-reported types of victimization in low-and lower-middle-income countries was 76.8% (Le, Holton, Romero, & Fisher, 2016). In the United States, a national study indicated that 80% of adolescents suffered from at least one type of victimization in their lifetime (Turner, Finkelhor, & Ormrod, 2010).…”
Section: Introductionmentioning
confidence: 99%